Influence of comorbidities not associated with fibromyalgia on neuropathic pain in patients with psoriatic arthritis: relationship with clinical parameters - Toledano, Esther; Queiro, Rubén; Gómez-Lechón, Luis; Chacón, Carolina Cristina; Hidalgo, Cristina; Ibañez, Marta; Díaz-Álvarez, Agustín; Montilla, Carlos (Frontiers in Medicine, 2024)
Objective Neuropathic pain (NP) may influence disease activity assessment in patients with psoriatic arthritis, this relationship being traditionally based on the presence of concomitant fibromyalgia. We analyzed the influence of other comorbidities on NP and the relationship between pain and various clinical parameters. Methods A cross-sectional study was conducted in patients diagnosed with psoriatic arthritis, excluding patients with a previous diagnosis of fibromyalgia, depression, anxiety, diabetes and/or dyslipidemia under treatment. NP was identified using the painDETECT questionnaire (score > 18). Obesity and related clinical parameters, anxious and depressive symptoms, sleep quality and fatigue were assessed as comorbidities. Disease activity was measured using the clinical Disease Activity Index for Psoriatic Arthritis (cDAPSA) in peripheral involvement, the ASDAS-PCR in axial involvement, functioning and disease impact were measured using the Health Assessment Questionnaire-Disability Index and 12-item Psoriatic Arthritis Impact of Disease questionnaire, respectively. Results Overall, 246 patients were included (136 men; 55%). The mean age was 53.4 ± 11.0 years. Forty-two patients had NP (17.1%). Patients with NP had higher leptin levels (OR: 1.03, 95% CI: 1.007–1.056; p < 0.01) and poor sleep quality (OR: 1.20, 95% CI: 1.09–1.297; p < 0.001). Patients with NP also had greater fatigue NRS (6.2 ± 2.2 vs. 2.4 ± 0.19, p < 0.001). Patients with NP had higher cDAPSA score (17.3 ± 5.4 vs. 8.9 ± 6.5, p < 0.001), poorer functioning (1.1 ± 0.5 vs. 0.4 ± 0.5, p < 0.001) and greater disease impact (6.1 ± 1.7 vs. 2.6 ± 1.9, p < 0.001). Conclusion NP was correlated with sleep quality and serum leptin and may be associated with worse disease activity, functioning and disease impact.